A blockchain-driven framework designed for pharmaceutical community to secure and trace the trail of drug supply chain - Rahman, Samiha; Aquib, Arif Awasaf; Jyoty, Watry Biswas; Rahman, Moshiur; Dewan, Tamanna (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.